The Moral Threat of Compartmentalization: Self, Roles and Responsibility - Rozuel, Cécile (2011)
Although most of us understand and accept that we play different roles in different settings, the moral implications of an unquestioned role-based world are serious. The prevalence of roles at the expense of ‘real’ people in organizations jeopardizes our ability to exercise full moral agency and ascribe moral responsibility, because ‘we were only fulfilling our role obligations’. This reasoning does not sustain ethical scrutiny, however, because individuals are always present behind the role, though they may lack awareness of their ability to choose and act as fully fledged individuals. The article argues that moral responsibility requires us to move away from a role-based life game which leads us to compartmentalize and forget who we are and what we value at a significant cost. On the contrary, an understanding of the process of compartmentalization and a greater awareness of the complex yet holistic nature of the self contribute to furthering moral integrity and responsibility.
Keywords: Self; Role; Responsibility; Persona; Moral Agency; Jung; Compartmentalization